Cell type-specific profiling of protein-DNA interactions without cellisolation using Targeted DamID with next-generation sequencing - Southall,TD; Marshall,OJ; Brand,AH (Nature Protocols, 2016)
The ability to profile transcription and chromatin binding in a cell type-specific manner is a powerfulapproach for understanding cell fate specification and cellular function in multicellular organisms.We recently developed Targeted DamID (TaDa) to enable genome-wide, cell-type-specific profiling ofDNA- and chromatin-binding proteins in vivo without cell isolation. As a Protocol Extension, thisarticle describes substantial modifications to an existing Protocol and offers additional applications.TaDa builds upon DamID, a technique for detecting genome-wide DNA binding profiles of proteins,by coupling it with the GAL4 system in Drosophila to enable both temporal and spatial resolution.TaDa ensures that Dam-fusion proteins are expressed at very low levels, avoiding toxicity andpotential artefacts from over-expression. The modifications to the core DamID technique presentedhere also increase the speed of sample processing and throughput, and adapt the method to NextgenerationSequencing technology. TaDa is robust, reproducible, and highly sensitive. Compared toother methods for cell-type specific profiling, the technique requires no cell-sorting, crosslinking orantisera, and binding profiles can be generated from as few as 10,000 total induced cells. By profilingthe genome-wide binding of RNA polymerase II, TaDa can also identify transcribed genes in a celltype-specific manner. Here we describe a detailed protocol for carrying out TaDa experiments andpreparing the material for next generation sequencing. Although we developed TaDa in Drosophila, itshould be easily adapted to other organisms with an inducible expression system. Once transgenicanimals are obtained, the entire experimental procedure – from collecting tissue samples togenerating sequencing libraries – can be accomplished within 5 days.